2021
DOI: 10.1177/23259671211007878
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Knee Joint Position Sense Tests for Anterior Cruciate Ligament Injury: A Systematic Review and Meta-analysis

Abstract: Background: Knee proprioception is believed to be deficient after anterior cruciate ligament (ACL) injury. Tests of joint position sense (JPS) are commonly used to assess knee proprioception, but their psychometric properties (PMPs) are largely unknown. Purpose: To evaluate the PMPs (reliability, validity, and responsiveness) of existing knee JPS tests targeting individuals with ACL injury. Study Design: Systematic review; Level of evidence, 4. Methods: PubMed, Allied and Complementary Medicine, CINAHL, SPORTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 117 publications
(431 reference statements)
2
45
1
Order By: Relevance
“…Although one study by Roberts et al [ 22 ] reported the standard error of measurement (SEM; 0.003°to 0.24°) for their TTDPM outcomes, the overall RoB was rated “inadequate” (Additional file 4 : Table S4) because the study did not report whether the patients were stable between measurements (test–retest interval was one month). In our previous systematic review on the PMPs of knee joint position sense (JPS) tests [ 11 ] only three studies (with RoB ratings of “inadequate”) reported test–retest reliability and one study (with an RoB rating of “very good”) reported insufficient quality for intra-session reliability. In agreement with the current findings of the TTDPM tests, there is therefore a lack of evidence for the reliability of tests that attempt to assess kinesthesia, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one study by Roberts et al [ 22 ] reported the standard error of measurement (SEM; 0.003°to 0.24°) for their TTDPM outcomes, the overall RoB was rated “inadequate” (Additional file 4 : Table S4) because the study did not report whether the patients were stable between measurements (test–retest interval was one month). In our previous systematic review on the PMPs of knee joint position sense (JPS) tests [ 11 ] only three studies (with RoB ratings of “inadequate”) reported test–retest reliability and one study (with an RoB rating of “very good”) reported insufficient quality for intra-session reliability. In agreement with the current findings of the TTDPM tests, there is therefore a lack of evidence for the reliability of tests that attempt to assess kinesthesia, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Due to our search encompassing all tests of proprioception as part of our review series, further details of the study selection process are provided in our previous review [ 11 ]. Briefly, after removal of duplicates, two authors (AS, ET) independently screened all titles, abstracts and full texts of relevance according to the stated eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Research on shoulder and knee JPS indicates that statistically larger errors are found while the active reproduction is performed compared with passive reproduction of joint position. [ 42 , 49 ] Regarding the positioning of the participant when assessing shoulder proprioception, it has been found that there are no statistically significant differences in outcome, regardless of whether the participant is in a supine, sitting, or standing position [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that de cits in proprioception were not present among the individuals of our ACLR group, who were active and participated on average 23 months after surgical reconstruction. Additionally, a recent meta-analysis found that only knee JPS tests with passive rather than active movements differentiate between ACL-injured knees and those of asymptomatic controls 9 . The active movements of the current test, which also incorporated the hip, may further have contributed to the lack of between-group difference seen here.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes are based on the difference in degrees between the target and reproduced angles, thus re ecting the kinematic errors. Meta-analyses have found signi cantly greater knee JPS errors for ACLinjured knees compared to both the contralateral non-injured knees of the same individuals [7][8][9] and to those of asymptomatic persons 8,9 . The clinical signi cance of these ndings is however unclear given the small absolute differences of < 1° knee exion angle.…”
Section: Introductionmentioning
confidence: 99%